Environmental education on the public square, Botucatu city/SP - Moreira-Coneglian, Inara Regiane (2009)
Science teaching can be carried out in different ways, but practical activities make the teaching more meaningful and effective trough the involvement of the students with the subject. Environmental education which is part of the Science subject in the elementary school has been seen as a way to improve life quality, changing the students’ values and attitudes towards the environment. Public squares are the appropriated setting to develop methodology in environmental education because one can treat the subject in an interdisciplinary way (involving historical, natural and political aspects). There the students immediately apply the recently acquired knowledge in the preservation and care of historical buildings of their town. The activities carried out, both in school and at the square, were related to the perception of the environment and identification of problems and solutions, aiming to build responsibilities and civic awareness. The research was carried out at Isabel Arruda square, involving 41 students from the 6th grade of an elementary school from 09/11 to 10/04/2001.